Business Model for Community Based Sheep Breeding in Ethiopia - Bereket, Yemariam; Solomon, Rahel; Asnake, Woinshet; Getachew, Tesfaye; Haile, Aynalem; Rischkowsky, Barbara; Kassie, Girma (International Center for Agricultural Research in the Dry Areas, 2023)
Small ruminant community-based breeding refers to a breeding program managed and implemented by business-oriented livestock keepers, aiming to improve the genetic potential of their small ruminant populations. The community-based breeding program is well suited for intensive market-oriented farming and requires a small breeding flock. According to the Central Statistical Agency, Ethiopia's total sheep and goat population is estimated at 95.4 million, where 42.9 million are sheep and the remaining 52.5 million are goats (CSA, 2021). This abundance of animals contributes significantly to the country's economy and food security. Livestock farming is critical to meeting the population's dietary demands and provides work for many Ethiopians, particularly in rural areas. These indigenous small ruminant breeds have adapted to their surroundings and have characteristics that make them resistant to adverse situations like drought and disease. This genetic diversity ensures the survival of these animals and serves as a significant resource for future breeding initiatives aimed /at improving their performance. Small ruminant production in Ethiopia is characterized by its low productivity due to, inter alia, limited access to improved genetics, poor nutrition, inadequate healthcare, lack of access to finance, and lack of knowledge on proper animal management practices. Community-based breeding programs (CBBP) can address the challenges associated with accessing improved genetics. CBBP helps livestock keepers to access high-quality breeding stock. There is a wealth of scientific evidence on the benefits of CBBP in different parts of Ethiopia. The demand for improved CBBP breeding sires, and other products such as meat animals, and ultrasonography is very high. However, there is no self-motivated entrepreneurship around CBBP in the country. Therefore, we formulated a comprehensive business model that details the different aspects related to the establishment, management, and financial feasibility of a community-based sheep breeding business (CBSBB) in three locations. The three locations are Bonga, Doyo Gena, and Menz. These are areas where the technical and economic feasibility of CBBP has been tested for more than a decade.